Rare bird documentation form for Peregrine Falcon at Dunbar Slough, 1980 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1980)
Rare bird documentation form for a Peregrine Falcon at Dunbar Slough in Greene County, IA on September 21, 1980. Epson - sheet feed